Patterns of attention towards circular economy practices: Insights from the metal industry in Estonia - Arseni Kotov (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
The imperative need for sustainable development has driven the integration of the circular economy into strategic agendas across diverse industries. The circular economy offers a promising approach to mitigating environmental impacts, reducing costs, and generating alternative revenue streams through circular business model strategies. In energy-intensive sectors, such as the metal industry, where carbon emissions are significant, circular economy practices present pathways for enhancing resource efficiency and achieving energy savings. Despite these benefits and technological feasibility, the adoption of circular economy remains limited. This study applies the attention-based view of the firm to explore the factors shaping managerial attention on circular economy practices within the metal industry in Estonia. Through a thematic analysis of interview-based secondary data, a number of internal and external factors were identified. The findings contribute to the limited empirical research on circular economy adoption in this context, offering insights for researchers and practitioners focused on sustainability transitions. Additionally, this study addresses the limited research on circular economy practices in Estonia, providing perspectives to support further advancement of circular economy adoption in the country. The results offer practical guidance for decision-makers navigating the complexities of implementing the circular economy and highlight the role of managerial attention as a relevant component in strategic decision-making for sustainable development.
Keywords: Q01; Q56; L60; M14; O31; 330; Attention-Based View; Circular Economy; Circular Business Model; Metal Industry; Estonia